Evaluation of Educational Performance according to Centralization and Decentralization - Lafta, Abed Alsalam; Almousawy, Hasan Abed Almohsen (Journal of Economics and Administrative Sciences, 2021)
The research aims to identify the effect of applying administrative decentralization to an educational performance by assessing educational performance before and after the process of transferring powers from the federal government (the Iraqi Ministry of Education) to local governments (governorates) as well as identifying the appropriate central or decentralized administrative system to advance the educational reality and performance. To achieve the goal of the research, educational data was collected and analyzed, as well as the measurement of educational performance indicators and analysis during two phases, the first represents the stage of applying the central system and spanned between the academic year (2011-2012) and the academic year (2014-2015), while the second phase, which represents the phase of applying the decentralized system, extended Between the academic year (2015-2016) and the academic year (2018-2019). The research community was formed in all education directorates in the governorates of Iraq, except for the Kurdistan region, with the exception of the following governorates (Kirkuk, Anbar, Salah al-Din, and Nineveh) due to the lack of educational data at the ministry due to the security conditions witnessed, while the research sample was represented in eleven governorates (Diyala, Baghdad, Babil, Karbala, Najaf, Al-Qadisiyah, Muthanna, Wasit, Thi Qar, Maysan, Basra), and the researcher calculated the arithmetic averages and the upper and lower limits for each of the educational data and educational indicators in the governorates in the field of research during the two periods (central and decentralization) and then a comparison between them Using the ratio of the German and Teni method to determine the presence of significant differences between performance indicators in the two phases and to determine which is better. The research found that the transition to a decentralized system and the process of transferring powers between the Iraqi Ministry of Education and the provinces has negatively affected educational performance, and the researcher recommended a set of recommendations to advance the educational reality in Iraq, the most important of which is reviewing the transfer of powers and also recommended measures that improve educational performance